Waterscape and Floods Management of Greek Selinus: The Cottone River Valley - Mazza Alba (De Gruyter, 2021)
This paper investigates water bodies in the Greek colony of Selinus, Western Sicily-Italy. It focuses especially on one of the two rivers of the city: the Cottone. The investigative strategy adopted in this study consists of an interdisciplinary approach based on the analysis of archaeological evidence, Earth Sciences data, and the study of historical cartography. Results indicate that the Cottone River was not a swampy and unhealthy intermittent stream as it was believed so far; it was instead a fully functional water body featuring an active floodplain. Most importantly, research presented in this article indicates several floods occurred in Selinus from the second or third quarter of the sixth century BC to the end of the fifth century BC. These floods, which occurred at the peak of Selinus’ cultural and economic life, were related to severe major events, rather than seasonal floods, as suggested by other scholars. The management of these floods and the waterscape was crucial to the city’s prosperity. This article also analyzes the relationship between the Cottone River and the fortification walls located at the Cottone River Valley. Results indicate that the fortification walls functioned not only as a defensive infrastructure, but also as a hydraulic engineering solution for flood retention. A better understanding of the environment in which Selinus was settled is now available, and knowledge on the importance of waterscapes and their management has been enhanced.